2005
DOI: 10.5617/nordina.495
|View full text |Cite
|
Sign up to set email alerts
|

Alfa and Omega in Student Assessment. Exploring Identities of Secondary School Science Teachers

Abstract: The dissertation is aiming at investigating the identity formation of the secondary school science teachers. The core phenomenon is student assessment, and more specific epistemological and ideological assets and dilemmas of student assessment as teacher identity formation. Student assessment has grown in number of purposes and has been extended due to institutionalization as well as multifold educational agendas. However, student assessment seen as the challenges teachers are facing and their reflection about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 131 publications
1
6
0
1
Order By: Relevance
“…This study reveals a tension between the school subject as a construct for grading and universal system (national regulations) for grading constructs. Previous studies have found similar results and suggested that controversy can occur when there is a mismatch between the theories and epistemologies that drives the instructional activities and assessment processes (Eggen 2004:480, Brookhart 1994, Stiggins et al 1989, Airasian & Jones 1993. In this study this becomes evident when grades are aggregated at the system level and comparisons are made between grades in mathematics (informants report that they always use all six grades) and Norwegian (informants report that they never use grade 1 and seldom use grade 6); this clearly compromises comparability.…”
Section: Mismatch Of Epistemologies and Validity Of Gradessupporting
confidence: 58%
See 2 more Smart Citations
“…This study reveals a tension between the school subject as a construct for grading and universal system (national regulations) for grading constructs. Previous studies have found similar results and suggested that controversy can occur when there is a mismatch between the theories and epistemologies that drives the instructional activities and assessment processes (Eggen 2004:480, Brookhart 1994, Stiggins et al 1989, Airasian & Jones 1993. In this study this becomes evident when grades are aggregated at the system level and comparisons are made between grades in mathematics (informants report that they always use all six grades) and Norwegian (informants report that they never use grade 1 and seldom use grade 6); this clearly compromises comparability.…”
Section: Mismatch Of Epistemologies and Validity Of Gradessupporting
confidence: 58%
“…The total sample consisted of 41 teachers: 19 from lower secondary schools and 22 from upper secondary schools. Slightly more than half (24) , Melograno 2007, Eggen 2004, Black et al 2003, **Norwegian is here seen as equal to studies that have included subjects of first language are women. The distribution of those interviewed is balanced across the selected school subjects, educational levels and the six schools.…”
Section: Sample and Selection Strategymentioning
confidence: 89%
See 1 more Smart Citation
“…Although, the idea of children's assessment is not new to them and all three reported using the portfolio as a way of assessing children's progress (as suggested by the national early childhood curriculum), none of them seemed to perceive assessment as an integral part of teaching and learning, let alone as a dialogue between teachers, learners, and their families. Their approach to assessment, although not stated explicitly, seems to be more teacher-centred than child-and family-centred (Eggen 2004). In other words, they seem to view parents as consumers of assessment ('they all get the portfolio at the end of the year') and children's 'words' as 'cute' (rather than giving an insight into children's thinking and development).…”
Section: Discussionmentioning
confidence: 93%
“…At laerere setter karakterer med utgangspunkt i andre egenskaper hos eleven enn fag, er en velkjent problemstilling i internasjonal forskning om vurdering. Ofte forklares en slik praksis med et manglende samsvar mellom laereres og skolemyndigheters oppfatninger om hva som utgjør et godt grunnlag for vurdering av prestasjoner (Angelo, 1998;Brookhart, 1991Brookhart, , 2013Manke & Loyd, 1990;Stiggins, Frisbie & Griswold, 1989;Eggen, 2004;Resh, 2009). Det er for eksempel dokumentert at innsats og aktivitet tas med i laereres karaktervurdering (Throndsen, Hopfenbeck, Lie & Dale, 2009;Prøitz & Borgen, 2010), og at elevgruppers sosiale bakgrunn også kan ha en påvirkning på laereres karaktersetting (Haegeland, Kirkebøen, Raaum & Salvanes, 2005).…”
unclassified